Report of Nestle / Aslam Mahadi Aslam Mahadi, Nur Syahida Azma Mohd Yusoff and Nurul Hazwani Joaini - Mahadi, Aslam; Mohd Yusoff, Nur Syahida Azma; Joaini, NurulHazwani (2008)
Nestlé was founded in 1860. In the 1860s Henri Nestlé, a pharmacist, developed a food for babies whose mothers were unable to breastfeed. His first success was a premature infant who could not tolerate his own mother's milk or any of the usual substitutes. The value of the new product was quickly recognized when his new formula saved the child's life, and soon, Farine Lactée and Henri Nestlé was being sold in much of Europe. In 1905 Nestlé merged with the Anglo-Swiss Condensed Milk Company. By the early 1900s, the company was operating factories in the United States, United Kingdom, Germany and Spain. World War I created new demand for dairy products in the form of government contracts. By the end of the war, Nestlé's production more than doubled